Community Empowerment through Pharmaceutical Technology: Post-Harvest Rhizome Utilization and Product Packaging Skills Enhancement at Kebun Merdesa, Cikarawang Village, Bogor Regency - Utami, Novi Fajar; Amaliasari, Diana; Jayawinangun, Roni; Rahmawati, Yelni; Adnan, Vanya Nafiza Putri; Apriansyah, Rafli (International Journal of Research in Community Services, 2025)
This study presents a community service initiative aimed at empowering a rural community in Indonesia through training in the post-harvest utilisation of rhizomes using pharmaceutical technology, packaging design, and digital marketing. The project involved 20 participants from the Kebun Merdesa community and was conducted by a team of three lecturers and seven students from the University of Pakuan. The training was divided into several stages, including the production of herbal tea, herbal drinks, and kitchen spices, followed by packaging design using the Canva and Pacdora applications and digital marketing using social media platforms and the Buffer application. The results showed significant improvements in the participants' knowledge and skills across all areas, with increases ranging from 31% to 34% in rhizome processing, herbal product manufacturing, packaging design, and digital promotion. These findings align with previous studies that have highlighted the effectiveness of targeted training programs in enhancing participants’ competency in specialised skill areas. The integration of technical production, innovative packaging, and digital marketing has been shown to significantly impacts the economic resilience and competitiveness of small enterprises in rural areas. This initiative demonstrates a practical model for rural community empowerment that can be replicated in other agricultural areas with similar resources and challenges, supporting the Sustainable Development Goals of decent work, economic growth, and responsible consumption and production. The success of this program provides a strong argument for policy support and funding for community-based pharmaceutical product development, contributing to the resilience of rural economies against market fluctuations and climate-related agricultural risks